1992
DOI: 10.1139/y92-170
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal magnesium metabolism in two rat models of genetic hypertension

Abstract: Magnesium concentrations in erythrocyte ghosts and arterial tissue of male, spontaneously hypertensive rats (SHR) were significantly less than in these tissues of male normotensive controls (Wistar-Kyoto; WKY) of the same age, which were also fed rat chow and tap water. The magnesium concentration in SHR erythrocyte ghosts was increased to the control value by incubating SHR erythrocytes with WKY blood plasma; SHR plasma did not affect the magnesium concentration in WKY erythrocyte ghosts. The magnesium concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 11 publications
2
8
1
Order By: Relevance
“…These in vivo and immunocytochemical observations suggest that NERPs are involved in the central control of body fluid balance. Consistent with previous reports (25,26), icv injection of hypertonic NaCl or AII increased plasma vasopressin levels in rats (Fig. 4C, 2nd and 11th lanes).…”
Section: Characterization and Identification Of Nerp-1 And Nerp-2-supporting
confidence: 93%
See 1 more Smart Citation
“…These in vivo and immunocytochemical observations suggest that NERPs are involved in the central control of body fluid balance. Consistent with previous reports (25,26), icv injection of hypertonic NaCl or AII increased plasma vasopressin levels in rats (Fig. 4C, 2nd and 11th lanes).…”
Section: Characterization and Identification Of Nerp-1 And Nerp-2-supporting
confidence: 93%
“…Vasopressin release is regulated by the electrical activity of vasopressin neurons, which are modulated by various neurotransmitters and neuromodulators (25,26). The major neural signals to vasopressin neurons are excitatory and inhibitory postsynaptic currents generated by presynaptic release of glutamate and ␥-aminobutyric acid, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, in contrast to the results predicted by this hypothesis, the present study reveals that platelet [Mg2+]i was increased and serum Mg2+ was unaltered in SHR in the present study. Many investigators have shown decreased [Mg2+]i in erythrocytes and platelets in essential hypertension (16-18) and in erythrocytes and cardiac tissue in SHR (19)(20)(21). The reason for these discrepancies between our present findings and those of previous reports is not clear but may be due to the differences in cell types studied and the methods used for [Mg2+]i assessment.…”
Section: Discussioncontrasting
confidence: 99%
“…For example, it has been suggested that there is an important connection between elevated [Ca2+]i and increased Na+/ H+ exchange activity (12) or intracellular Na+ accumulation via suppression of Na+/K+ATPase (13, 14). Furthermore, a number of reports have shown Mg2+ deficiency at the cellular or systemic levels in essential hypertensive patients (9, 15-18) and genetically hypertensive rats (19)(20)(21), although a few studies have not (22,23). In theory, Mg2+ deficiency in the cytosol may account for decreases in Ca2+-ATPase and Na+/K+ATPase and increases in Na+-Ca2+ exchange, thereby leading to increased intracellular Ca2+ concentrations (24,25).…”
Section: Introductionmentioning
confidence: 99%
“…11,14,28,29 In humans, the occurrence of Mg 2ϩ deficiency and the benefits of Mg 2ϩ supplementation have been debated, largely by which end point and how to measure Mg 2ϩ . 30 -33 However, even small alterations in Mg 2ϩ might induce vascular alterations, increasing the risk for cardiovascular-related conditions.…”
Section: Discussionmentioning
confidence: 99%